Basic principles and categories of synergetic theory as a methodological basis of terorology - Канцір, Володимир Степанович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article deals with synergetic ways during modelling of state and legal proceses, especially the phenomenon of international terrorism - multifunctional, system and social phenomenon.